Communicating Cultural Instituion: A Treatise of Indonesian Ulama in Different Technological Eras - Baihaky, Rachmat; Fuaida, Lisma Dyawati (Nyimak: Journal of Communication, 2024)
The development of technology is one of the determining factors of social change. While cultural groups reject this postulate, indicating that political and economic powers are the ones responsible for the emergence of technology as a driver of these changes, it certainly challenges old conclusions regarding social change. One tangible manifestation of this phenomenon is the advancement of communication technology, which has significantly transformed traditional processes in the production, distribution, and reception of messages among the public. In the realm of religion, the development of communication technology has empowered cultural institutions to reach their followers. In the context of religious leaders in Indonesia, the penetration of religious messages within the community varies significantly when viewed through the lens of each technological advancement in its respective era. This research attempts to elaborate on the journey of da’wah (Islamic preaching) in Indonesia by examining its approaches through the use of different communication technologies across various times. Furthermore, this study discusses the implications of these changes on the self-perception of ulama and the broader Muslim community. This research contributes to the field of communication studies by revealing the dynamic interaction between technology, identity, and religious authority in contemporary Indonesia, while emphasizing the need for ongoing discussions about the role of cultural institutions in shaping societal values and beliefs.Keywords: Communication, Da’wah, Ulama, Technology. AbstrakPerkembangan teknologi menjadi salah satu faktor penentu dari perubahan sosial. Meskipun kelompok kulturalis menolak postulat ini, dengan megindikasikan kekuatan politik dan ekonomilah yang menyebabkan kehadiran teknologi selaku pendorong perubahan tersebut. Hal ini tentu saja menguji kesimpulan-kesimpulan lama terkait perubahan sosial. Salah satu bentuk nyata dari fenomena ini adalah perkembangan teknologi komuniasi. Di mana dalam perkembangannya hal ini merubah secara signifikan proses-proses lama dalam produksi pesan, pendistribusian, dan penerimannya di tengah khalayak. Di bidang keagamaan, perkembangan teknologi komunikasi telah memberikan kekuatan terhadap institusi budaya ini dalam menjangkau pengikutnya. Pada konteks pemuka agama di Indonesia, penetrasi pesan agama di tengah ummat memiliki pengaruh yang sangat berbeda jika dilihat dari setiap perkembangan teknologi komunikasi di masing-masing era. Penelitian ini mencoba untuk mengelaborasi perjalanan da’wah di Indonesia dilihat dari pendekatannya dengan penggunaan teknologi komunikasi yang berbeda di setiap zamannya. Selanjutnya, penelitian ini membahas implikasi perubahan ini terhadap persepsi diri ulama dan komunitas Muslim yang lebih luas. Penelitian ini berkontribusi pada bidang studi komunikasi dengan mengungkapkan interaksi dinamis antara teknologi, identitas, dan otoritas keagamaan di Indonesia kontemporer, serta menekankan perlunya diskusi berkelanjutan tentang peran institusi budaya dalam membentuk nilai-nilai dan keyakinan masyarakat.Kata Kunci: Komunikasi, Da’wah, Ulama, Teknologi.